2015
DOI: 10.1073/pnas.1423099112
|View full text |Cite
|
Sign up to set email alerts
|

Continental crust beneath southeast Iceland

Abstract: The magmatic activity (0–16 Ma) in Iceland is linked to a deep mantle plume that has been active for the past 62 My. Icelandic and northeast Atlantic basalts contain variable proportions of two enriched components, interpreted as recycled oceanic crust supplied by the plume, and subcontinental lithospheric mantle derived from the nearby continental margins. A restricted area in southeast Iceland—and especially the Öræfajökull volcano—is characterized by a unique enriched-mantle component (EM2-like) with elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 65 publications
5
104
0
Order By: Relevance
“…The position of interpreted COBs is not sufficient to infer the presence of an additional continental tectonic block, as COB interpretations could be subjective. However, the gap in the reconstruction, plus evidence of buried continental crust under present-day SE Iceland, led Torsvik et al (2015) to suggest that the JMMC is much larger and its southern fragment, which is possibly buried under presentday SE Iceland, was rifted from the Greenland continental margin situated south of the Blosseville Coast (Fig. 5).…”
Section: Break-up and Early Seafloor Spreadingmentioning
confidence: 99%
“…The position of interpreted COBs is not sufficient to infer the presence of an additional continental tectonic block, as COB interpretations could be subjective. However, the gap in the reconstruction, plus evidence of buried continental crust under present-day SE Iceland, led Torsvik et al (2015) to suggest that the JMMC is much larger and its southern fragment, which is possibly buried under presentday SE Iceland, was rifted from the Greenland continental margin situated south of the Blosseville Coast (Fig. 5).…”
Section: Break-up and Early Seafloor Spreadingmentioning
confidence: 99%
“…Alternatively, a situation could be envisaged whereby the High-Ti melts were being produced within a more continuous melting region, with the LowTi lavas initially being fed into the High-Ti flow fields from an area of progressively thinning lithosphere to the west (e.g. The proposed site of the proto-Icelandic anomaly under either central (Lawver & Müller, 1994), or central east (Torsvik et al, 2015) Greenland at the time, could also potentially raise questions as to the presence of symmetrical melt columns on either side of the rift system. Upwelling mantle material convecting along the base of the lithosphere from the anomaly source (e.g.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Foulger & Anderson (2005) proposed the presence of a microplate that may contain oceanic crust submerged beneath younger lavas. Recently, Torsvik et al (2015) suggested the presence of a sliver of continental crust beneath SE Iceland that links with the JMMC. This interpretation is based on geochemistry data.…”
Section: Greenland -Iceland -Faroe Ridgementioning
confidence: 99%